Utilizing Customer Relationship Management in E-Tailing: Enhancing Sales of Two-Wheeler Products in the Indian Market - Christina Arundhati Sen, Swaroop Mohanty (European Economic Letters (EEL), 2024)
In aftermath of the COVID-19 pandemic, there has been a notable shift in consumer behavior towards online platforms for product exploration and purchasing. E-commerce retailers, particularly in the two-wheeler industry, are increasingly adopting customer relationship management (CRM) strategies, with a focus on leveraging social media channels, to boost sales. In this study the researchers have delved into understanding the impact of CRM on two-wheeler sales in India, specifically examining the effectiveness of social media marketing and its influence on purchasing decisions. By employing demographic analysis and statistical methods on data collected through Google Forms surveys, this research aims to uncover the crucial factors driving successful CRM implementation in the two-wheeler market.